Seasonal Effects of Daylight Conditions on Occupant Perception and Skin Temperature - Krüger, Eduardo (Frontiers in Sustainable Cities, 2022)
Current research on the relationship between daylight and well-being has shown that access to daylight plays a relevant role both in terms of light perception and with respect to physiological mechanisms not directly related to vision. The aim of this paper is to analyze changes in reported light perception and in physiological responses, represented in this case by the skin temperature of research participants (n = 16) across three seasons (winter, spring and summer seasons) in a temperate, mid-latitude location, Karlsruhe, in southern Germany (49°N, 8.5°E). Sessions have been held in thermally stable rooms of a climate chamber, with daylight exposure to two opposing solar orientations of the glazed façade, namely equatorial and non-equatorial orientations, over 5-h morning sessions. Differences in light perception as well as changes in physiology have been observed. Results showed an increased sensitivity of the individuals in terms of light perception to changes in daylight in winter while such sensitivity dropped in spring and summer, with greater daylight availability and diminished lighting variability during sessions. Due to the intrinsic relationship between light perception and circadian entrainment, the same was verified for changes in skin temperature, which were also found to be significantly related to daylight availability. Seasonal influence suggests that variability of brightness and correlated color temperature (CCT) of natural light can affect both psychological and physiological patterns in humans.